Effect of Passive Smoking during Pregnancy on Birth Weight of Neonates - Tahira Yasmeen, Razia Sultana, Tahira Khatoon, Saima Riaz, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Passive smoking during pregnancy is a risk factor for adverse pregnancy outcomes among neonates. Data on the correlation between passive smoking during pregnancy and birth weight of neonates remain limited and exposure to passive smoke during pregnancy is less clear, especially among Pakistani women. Objective: The aim was to determine the effect of passive smoking during pregnancy on birth weight of neonates. Methodology: This cross-sectional study was comprised of 320 mothers. The birth weight of neonates were compared among exposed and unexposed groups of passive smoking. A pre-designed structured questionnaire was used to record the details of exposure to passive smoking during pregenacy.The study was conducted in four tertiary care hospitals of Lahore Pakistan. Non-Probability Convenient sampling technique was used. Results: Results showed that from 320 women, 160 (50%) women were exposed to passive smoking and 160 (50%) women were unexposed to passive smoking. The exposed group 55(34.3%) had weight of neonate less than 2500 gram whereas 105 (65.6%) had normal birth weight of neonate and 10 (6.25%) of unexposed group had weight of neonate less than 2500 gram whereas 150 (93.7%) had normal birth weight of neonate. Though the incidence of low birth weight was more in the group exposed to passive smoking as compared to the unexposed group (34.3% vs. 6.25%).The differences were significant as p-value was <0.001. Conclusion: Exposure to passive smoking during pregnancy has a significant relationship with low birth weight of neonates.